Molecular biology of cancer-associated fibroblasts: can these cells be targeted in anti-cancer therapy? - Gonda, Tamas A. (2009)
It is increasingly recognized that the non-neoplastic stromal compartment in most solid cancers plays an active role in tumor proliferation, invasion and metastasis. Cancer associated fibroblasts (CAFs) are one of the most abundant cell types in the tumor stroma, and these cells are pro-tumorigenic. Evidence that CAFs are epigenetically and possibly also genetically distinct from normal fibroblasts is beginning to define these cells as potential targets of anti-cancer therapy. Here, we review the cell of origin and molecular biology of CAFs, arguing that such knowledge provides a rational basis for designing therapeutic strategies to coordinately and synergistically target both the stromal and malignant epithelial component of human cancers.